The effectiveness of exercise as treatment for vasomotor menopausal symptoms: randomised controlled trial. (17th December 2014) - Daley, AJ; Thomas, A; Roalfe, AK; Stokes‐Lampard, H; Coleman, S; Rees, M; Hunter, MS; MacArthur, C
<x xml:space="preserve">Abstract</x> Objective To investigate the effectiveness of exercise as treatment for vasomotor menopausal symptoms. Design Three‐group randomised controlled trial, two exercise interventions and a control group. Setting Primary Care, West Midlands UK. Population Perimenopausal and postmenopausal women experiencing at least five hot flushes/night sweats per day and not taken MHT in previous 3 months were recruited from 23 general practices. Methods Participants in both exercise interventions groups were offered two face‐to‐face consultations with a physical activity facilitator to support engagement in regular exercise. In addition, one exercise group received a menopause‐specific information DVD and written materials to encourage regular exercise and the other exercise group was offered the opportunity to attend exercise social support groups in their communities. Interventions lasted 6 months. Main outcome measure The primary outcome was frequency of hot flushes/night sweats at 6‐month up. Results Two hundred and sixty‐one women were randomised (n = 87 per group). Neither of the exercise intervention groups reported significantly less frequent hot flushes/night sweats per week than controls (exercise‐DVD versus control: −8.9, 95% CI −20.0 to 2.2; exercise‐social support versus control: −5.2, 95% CI −16.7 to 6.3). Conclusions This trial indicates that exercise is not an effective treatment for hot flushes/night sweats. Contrary to current clinical guidance, women should not be advised that exercise will relieve their vasomotor menopausal symptoms.